(untitled) (Research, Society and Development, 2020)
Breastfeeding is a beneficial practice in which the mother provides her child with all the necessary nutrients for a good physical, psychological, emotional and nutritional development. The objective was to carry out a bibliographic survey about the importance and benefits of breastfeeding. It is an integrative literature review, the search took place in the Virtual Health Library (VHL), with the help of the Latin American and Caribbean Literature in Health Sciences (LILACS), Scientific Electronic Library Online (SciELO), Nursing Database (BDENF) and PUBMED. The articles were collected from March to April 2020. The following keywords were used: Breastfeeding, Child’s health, Women’s health and Health promotion. After applying the inclusion criteria, 12 studies remained. It is concluded that breast milk is the appropriate food for the child, both from a nutritional and immunological point of view, as well as from a psychological point of view, because in addition to favoring the mother-child bond, it offers the nutrients that the child needs to start a healthy life, it is important that health professionals encourage and guide mothers as to their practice.